2015
DOI: 10.3906/zoo-1211-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessing age, growth, and reproduction of Alburnus mossulensis and Acanthobrama marmid (Cyprinidae) populations in Karakaya Dam Lake (Turkey)

Abstract: IntroductionThe freshwater fishes Alburnus mossulensis (Heckel, 1843) and Acanthobrama marmid (Heckel, 1843) are cyprinid fish found in the Euphrates and Tigris rivers in Turkey and their adjacent basins in Iran (Kuru, 1978;Coad, 2010). The distribution of A. mossulensis in Asia extends from the Tigris-Euphrates basin to the very upper parts of the delta of the Kor, Mand, and Kul rivers in Iran (Bogutskaya, 1997). A. marmid is present in the Tigris, Euphrates, and Orontes river systems, the Berdan River, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
7
0
3
Order By: Relevance
“…The condition factor of the same species in the Gamasiab River was between 0.20 to 2.51 for females and 0.32 to 2.01 for males (Mousavi-Sabet et al, 2013). Average condition factors in specimens in Karakaya Dam Lake were found to be 0.90 ±0.1 for females and 0.84 ± 0.11 for males (Uckun and Gokce, 2014). The condition factor of A. mossulensis species shows significant similarities compared to other species, such as Alburnus esherichii (Cetinkaya et al, 2015) and A. alburnus (Stavrescu-Bedivan et al, 2017).…”
Section: Condition Factormentioning
confidence: 89%
See 4 more Smart Citations
“…The condition factor of the same species in the Gamasiab River was between 0.20 to 2.51 for females and 0.32 to 2.01 for males (Mousavi-Sabet et al, 2013). Average condition factors in specimens in Karakaya Dam Lake were found to be 0.90 ±0.1 for females and 0.84 ± 0.11 for males (Uckun and Gokce, 2014). The condition factor of A. mossulensis species shows significant similarities compared to other species, such as Alburnus esherichii (Cetinkaya et al, 2015) and A. alburnus (Stavrescu-Bedivan et al, 2017).…”
Section: Condition Factormentioning
confidence: 89%
“…In two separate studies from the Karasu River, the fork lengths were in the range 85-185 mm and 94-195 mm (Turkmen and Akyurt, 2000;Yildirim et al, 2003), while the total lengths of individual specimens in Ataturk Dam Lake were 83-242 mm (Basusta and Cicek, 2006). Fork lengths of the species reported in Iran were 36-93 mm (Esmaeili and Ebrahimi, 2006) and the total lengths reported from Gamasiab River were 70-155 mm (Mousavi-Sabet et al, 2013) while the values in Karakaya Dam Lake were found to be between 108-190 mm (Uckun and Gokce, 2014). The difference in the size range in different localities is attributed to the changes in the biotic and abiotic factors between the environments and fishing periods (Emmrich et al, 2014).…”
Section: Length and Weight Compositionmentioning
confidence: 99%
See 3 more Smart Citations